High-throughput sequencing offers new insights into 5-hydroxymethylcytosine - Pang, Alina P.S. (Biomol Concepts, 2016)
Chemical modifications of DNA comprise epigenetic mechanisms that contribute to the maintenance of cellular activities and memory. Although the function of 5-methylcytosine (5-mC) has been extensively studied, little is known about the function(s) of relatively rarer and underappreciated cytosine modifications including 5-hydroxymethylcytosine (5-hmC). The discovery that ten-eleven translocation (Tet) proteins mediate conversion of 5-mC to 5-hmC, and other oxidation derivatives, sparked renewed interest to understand the biological role of 5-hmC. Studies examining total 5-hmC levels revealed the highly dynamic yet tissue-specific nature of this modification, implicating a role in epigenetic regulation and development. Intriguingly, 5-hmC levels are highest during early development and in the brain where abnormal patterns of 5-hmC have been observed in disease conditions. Thus, 5-hmC adds to the growing list of epigenetic modifications with potential utility in clinical applications and warrants further investigation. This review discusses the emerging functional roles of 5-hmC in normal and disease states, focusing primarily on insights provided by recent studies exploring the genome-wide distribution of this modification in mammals.